On (De)Constructing an Authoritative Narrative: The Case of The Letter of Isis - Blanco Cesteros, Miriam (ARYS. Antigüedad: Religiones y Sociedades, 2022)
The Letter of Isis to Horus is a brief (and precious) piece of Greco-Egyptian alchemy. Beyond the technical interest of the processes it describes, its prologue is noteworthy for its intricate and surprising mixture of Greek, Hebrew, and Egyptian elements. In it, alchemy is presented as a secret knowledge of divine origin, which the goddess Isis received from an angel who fell in love with her. This preface is, therefore, a key element in the study of the discursive mechanisms and arguments through which early alchemical tradition attempted to bestow authority on its writings and to justify the Holy Art label that is often conferred on this discipline. This article analyses these mechanisms and arguments according to the patterns around which this narrative was articulated.
Keywords: alchemy; demotic literature; Greco-Roman Egypt; Greco-Egyptian Magic; greek literature; Hermeticism; Rhetoric